Targeting host-specific metabolic pathways—opportunities and challenges for anti-infective therapy - Konaklieva, Monika I.; Plotkin, Balbina J. (Frontiers in Molecular Biosciences, 2024)
Microorganisms can takeover critical metabolic pathways in host cells to fuel their replication. This interaction provides an opportunity to target host metabolic pathways, in addition to the pathogen-specific ones, in the development of antimicrobials. Host directed therapy (HDT) is an emerging strategy of anti-infective therapy, which targets host cell metabolism utilized by facultative and obligate intracellular pathogens for entry, replication, egress or persistence of infected host cells. This review provides an overview of the host lipid metabolism and links it to the challenges in the development of HDTs for viral and bacterial infections, where pathogens are using important for the host lipid enzymes or producing their own analogous of Lecithin-Cholesterol Acyltransferase (LCAT) and Lipoprotein Lipase (LPL) thus interfering with the human host's lipid metabolism.